Perspectives in Carbonate Geology 2009
DOI: 10.1002/9781444312065.ch3
|View full text |Cite
|
Sign up to set email alerts
|

A Re‐Evaluation of Facies on Great Bahama Bank I: New Facies Maps of Western Great Bahama Bank

Abstract: A re-evaluation of the sediment distribution patterns on western Great Bahama Bank shows a facies distribution with two end-members. Coarse-grained sediments in the north, west, and south of the bank surround a mud-dominated realm located on the western leeward side of Andros Island. This facies distribution is comparable to earlier maps, but shows considerably more details and a complex distribution from grainstones to mud-rich wackestones. As in other carbonate platforms, sediment distribution appears to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(135 citation statements)
references
References 49 publications
5
130
0
Order By: Relevance
“…This is similar to the shallow subtidal lagoon protected by oolitic shoals in the Great Bahama Bank in which mud and pellet facies-belts are complexly distributed (e.g. Purdy, 1963;Halley et al, 1983;Reijmer et al, 2009;Harris et al, 2015). In fact, in the lagoon of the Great Bahama Bank the percentage of mud increases towards the coast of Andros Island (e.g.…”
Section: Interpretation Of Facies Association Bmentioning
confidence: 71%
See 1 more Smart Citation
“…This is similar to the shallow subtidal lagoon protected by oolitic shoals in the Great Bahama Bank in which mud and pellet facies-belts are complexly distributed (e.g. Purdy, 1963;Halley et al, 1983;Reijmer et al, 2009;Harris et al, 2015). In fact, in the lagoon of the Great Bahama Bank the percentage of mud increases towards the coast of Andros Island (e.g.…”
Section: Interpretation Of Facies Association Bmentioning
confidence: 71%
“…Wilkinson and Drummond, 2004;Suarez-Gonzalez et al, 2015), as it has been reported in numerous modern systems, such as Bahamas (e.g. Bathurst, 1975;Reijmer et al, 2009;Kaczmareck et al, 2010;Harris et al, 2015), Persian Gulf (e.g. Wagner and Van der Togt, 1973;Wilkinson and Drummond, 2004), Antigua (e.g.…”
Section: Depositional System and Evolution Of The Studied Units In Thmentioning
confidence: 99%
“…The Bahamas are a vast system of carbonate platforms (150,000 km 2 ) stretching in a NNW-SSE direction. Reefs, ooid shoals, or low-relief islands border the shallow-water areas of the platforms in which non-skeletal mud-rich sediments dominate (Purdy 1963a, b;Reijmer et al 2009;Fig. 2).…”
Section: Regional Geology and Geographymentioning
confidence: 99%
“…3, 6). The non-skeletal grains mainly consist of peloids, pellets, and ooids, grains that dominate the facies realms in the interior of Great Bahama Bank (Purdy 1963a, b;Enos 1974;Reijmer et al 2009) (Fig. 7).…”
Section: Summary Of Calciturbidites and Calcidebritesmentioning
confidence: 99%
“…For example, aragonite needles represent up to 85-90% of the fine sediments on the Bahama banks (Milliman 1974;Heath and Mullins 1984;Reijmer et al 2009). Their origin has been extensively discussed with authors supporting a biogenic origin and others favouring inorganic precipitation.…”
Section: Introductionmentioning
confidence: 99%